Emergent informal use of doxycycline post- and pre-exposure prophylaxis among men who have sex with men and transgender and gender diverse people, the Netherlands, 2024 - Teker, Buhari; Hoornenborg, Elske; Schim van der Loeff, Maarten F; Boyd, Anders; Heijne, Janneke CM; Prins, Maria; Davidovich, Udi; de Vries, Henry JC; Jongen, Vita W (Euro surveillance : bulletin européen sur les maladies transmissibles, 2025)
BACKGROUNDDoxycycline post-exposure and pre-exposure prophylaxis (doxyPEP/PrEP) to prevent sexually transmitted infections (STIs) is not part of standard practice in the Netherlands but may be used informally (without prescription).AIMWe assessed informal use and intention to use doxyPEP/PrEP among men who have sex with men (MSM) and transgender and gender diverse people in the Netherlands.METHODSBetween 26 February and 6 May 2024, we conducted an online survey on informal doxyPEP/PrEP use in the preceding 6 months and intention to use. We assessed the determinants of recent informal use and high intention to use using risk ratio regression.RESULTSOf the 1,633 participating individuals (96.7% MSM) 246 (15%) reported doxyPEP/PrEP use in the preceding 6 months. Informal use was more common among participants who used HIV PrEP or were living with HIV, had ≥ 15 anonymous sexual partners, engaged in chemsex, wanted to protect themselves, got advice from others to use doxyPEP/PrEP and believed doxyPEP/PrEP is safe. High intention to use (n = 1,063 (65%) participants) was more common among participants using HIV PrEP or living with HIV, who wanted to have condomless sex, who wanted to protect others from STIs and who perceived doxyPEP/PrEP as effective and safe.CONCLUSIONAlthough doxyPEP/PrEP is not formally recommended in the Netherlands, survey participants reported informal use and a high intention to use. These findings, combined with the global increase of antimicrobial resistance (AMR), stress the need for close monitoring and further research on the AMR effects of doxyPEP/PrEP use.